Parallel decoding cyclic burst error correcting codes - Umanesan, G.; Fujiwara, E. (IEEE transactions on computers, 2005)
Burst error correcting codes, such as fire codes, have traditionally been decoded using linear feedback shift registers (LFSR). However, such sequential decoding schemes are not suitable for modern ultra high-speed channels that demand high-speed parallel decoding employing only combinational logic circuitry. This work proposes a parallel decoding method for cyclic burst error correcting codes. Under this method, a binary companion matrix T defines the entire decoding process. Hence, the decoding method can be implemented using only combinational logic.